2002
DOI: 10.1212/wnl.58.11.1680
|View full text |Cite
|
Sign up to set email alerts
|

A crossover, add-on trial of talampanel in patients with refractory partial seizures

Abstract: The authors report a double-blind, placebo-controlled, crossover study of talampanel in 49 patients with refractory partial seizures. Three doses of talampanel were investigated based on differences in patients' concomitant antiepileptic drug usage. Talampanel showed efficacy in reducing seizure frequency (p = 0.001) with a median seizure reduction of 21%. Eighty percent of patients had fewer seizures on talampanel than on placebo. Dizziness (52%) and ataxia (26%) were the only significant adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 7 publications
0
65
0
Order By: Relevance
“…A third compound, the competitive AMPA/kainate receptor antagonist NS1209 has been studied in status epilepticus but the results have not been made available (64). In a small adjunctive trial in patients with refractory partial seizures, orally-administered talampanel appeared to show efficacy (65). However, because of pharmacokinetic interactions (talampanel plasma concentrations are markedly reduced in the presence of enzyme-inducing AEDs), the results were inconclusive.…”
Section: Human Studies With Ampa Receptor Antagonists In the Treatmenmentioning
confidence: 99%
“…A third compound, the competitive AMPA/kainate receptor antagonist NS1209 has been studied in status epilepticus but the results have not been made available (64). In a small adjunctive trial in patients with refractory partial seizures, orally-administered talampanel appeared to show efficacy (65). However, because of pharmacokinetic interactions (talampanel plasma concentrations are markedly reduced in the presence of enzyme-inducing AEDs), the results were inconclusive.…”
Section: Human Studies With Ampa Receptor Antagonists In the Treatmenmentioning
confidence: 99%
“…One 2,3-benzodiazepine, talampanel (GYKI 53773; LY300164), has shown efficacy in clinical trials. 262,263 Nonetheless, it is unclear whether AMPA receptor antagonists will be tolerable at therapeutic doses. In animal models, such agents generally cause neurological impairment at doses near those that confer seizure protection.…”
Section: Ionotropic Glutamate Receptorsmentioning
confidence: 99%
“…Both GYKI 53405 and talampanel are protective in the MES test in mice and also in various chemoconvulsant models, but only at doses near those that cause motor side effects (Andrási, 2001). In clinical trials talampanel has been reported to be well tolerated, but sedation may occur, especially with initial dosing (Chappell et al, 2002;Langan et al, 2003;Danielsson et al, 2004).…”
Section: Ampa Receptor Antagonistsmentioning
confidence: 99%